System architecture patterns: A consumer electronics domain based proposition - Ramasubramaniam, K.; Annamalai, G.; Krishna, Aneesh (2015)
This paper proposes system architecture patterns (similar to software architecture patterns) and also describes the practical experiences of designing the system architecture of a "combo" product (eg DVD player/recorder combined with TV, Set top Box functionality with Android application ecosystem etc.) based on two separate heterogeneous system architectures. We have proposed five system architecture patterns (currently) via which such combo system architectures can be derived. The first is a simple combination with minimal modifications pattern (SiCo) whereby the external interfaces (both software and hardware) are matched from a final product perspective. The second is a combination with modifications (CoMo) whereby considerable modifications are made to the system from a software and hardware perspective. The third is a central controller pattern (CC) whereby each subsystem exports its key states to a central controller which in turn manages the subsystems and the overall product use cases. The fourth is a Redesign and Re-architect pattern (RDRA), which will re-use certain key components from the independent subsystems but otherwise it is basically a back-to-drawing-board approach. The fifth is an Independent Standalone Subsystems (ISS) pattern whereby the 2 subsystems co-exist without any overlapping use-cases. The details of each pattern are explained together with the scenarios where they can be used. Some examples for each scenario are also highlighted. Some of our practical experiences in the industry are also highlighted. Note:-Mechanical packaging is not considered in this scope.